Abstract 126: Bilateral Limb Shaking TIA secondary to Severe Bilateral Carotid Stenosis - Muhannad Seyam; Michael Hehir; Fatemeh Sobhani (Stroke: Vascular and Interventional Neurology)
Introduction A case describing bilateral limb shaking episodes in a patient with severe bilateral carotid disease ‐ a rare manifestation of limb‐shaking TIA. Methods '‐ Results CASE A 71‐year‐old male patient with a past medical history significant for type 2 diabetes mellitus and bilateral carpal tunnel syndrome is being followed for symptomatic management of known axonal sensorimotor diabetic polyneuropathy in the neuromuscular clinic. He reported on one of his follow‐up visits that he had been experiencing an eight‐month history of presyncopal to syncopal events occurring solely in the standing position, not followed by postictal state but amnesia to the syncope itself, and resulting in falls with mild injuries. He was experiencing new‐onset dry eyes and mouth but denied anhidrosis or early satiety, and cardiac event monitoring during one of these events was unremarkable for rhythmic causes. Examination was unchanged from previously and was significant for findings consistent with length‐dependent sensory loss with hyporeflexia/areflexia. The constellation of symptoms was suggestive of autonomic dysfunction, and while this may be seen with diabetic polyneuropathy, workup for alternative autonomic neuropathies (including SSA/SSB antibodies, paraneoplastic antibody panel, serum protein electrophoresis with immunofixation, serum free light chains, transthyretin amyloid) was obtained with plan for follow‐up. A few months later, he presented to the ED with intermittent upper extremity shaking (more pronounced on the right than on the left) preceding the syncopal events, which only occurred in the standing position or during physical activity and resolved with rest. There were no (transient) focal neurological deficits, including monocular vision loss or hemispheric syndrome. CTA of the head/neck was obtained and was notable for severe to critical stenoses of the bilateral internal carotid arteries (see figure 1). Duplex US revealed 80‐99% stenosis of both right and left proximal internal carotid arteries. The constellation of findings was most suggestive of bilateral limb‐shaking TIA secondary to bilateral carotid stenosis. He was started on secondary stroke prevention and referred to vascular surgery for evaluation of revascularization. The patient underwent left carotid endarterectomy briefly afterward and experienced resolution of the events – he later also underwent carotid endarterectomy of the right side and remains asymptomatic. DISCUSSION: Limb‐shaking TIA is a well‐described yet underrecognized manifestation of severe carotid disease reported by C.M. Fisher in 1962. The “limb shaking” episodes are typically unilateral, affecting the arm or leg, and are often mistaken for seizures [1]. Pathogenesis involves hemodynamic impairment related to extracranial/intracranial carotid stenosis or occlusion resulting in stereotypical recurrent contralateral limb shaking episodes precipitated by physical activity [2], [3]. The constellation of “limb shaking” spells precipitated upon standing or physical activity with resolution after activity cessation should raise suspicion for limb‐shaking TIA and warrant vascular imaging. Treatment includes medical secondary stroke prevention and revascularization procedures [4], which can alleviate or even resolve the transient symptoms [2]. Conclusion Limb‐shaking TIA is an important yet underrecognized manifestation of relative cerebral hypoperfusion related to severe cerebrovascular disease. This case describes bilateral limb shaking episodes in a patient with severe bilateral carotid disease ‐ a rare manifestation of limb‐shaking TIA.